The Last olympian - Riordan, Rick (New York : Scholastic, 2009)
All year the half-bloods have been preparing for battle against the Titans, knowing the odds of victory are grim. Kronos's army is stronger than ever, and with every god and half-blood he recruits, the evil Titan's power only grows. In this momentous final book in the New York Times best-selling series, the long-awaited prophecy surrounding Percy's sixteenth birthday unfolds. And as the battle for Western civilization rages on the streets of Manhattan, Percy faces a terrifying suspicion that he may be fighting against his own fate.